The phenomenographic approach in research on second language learning - Nerlicki, Krzysztof (Glottodidactica, 2020)
The phenomenographic approach in educational research dates back to the early1980s. Marton and his co-workers focused on the significant role which is played by the individual beliefs of learners in the processes of teaching and learning. The study of learning experiences, reflections on these experiences and verbalization of these reflections have defined a new perspective in the perception of educational reality. The paper presents the basic assumptions of the phenomenographic approach and its application in the study of foreign language learners’ beliefs. Since beliefs result from many factors, among others of a socio-cultural nature, particular attention is paid to the dynamics of how beliefs are shaped in the light of the Activity Theory proposed by Vygotsky and his successors Leontiev and Engerström. The paper finishes with a discussion on the prospects of the study of beliefs in the Polish educational context, with particular consideration of foreign language philology students.